MANAJEMEN KEWIRAUSAHAAN PESANTREN DALAM MENUMBUHKAN JIWA ENTREPENEUR - Zahra Khusnul Latifah; Veni Ayu Rahmayanti (Universitas Djuanda, 2017)
Manajemen kewirausahaan pesantren adalah unsur dalam pendidikan yang dapat mensukseskan dan memperlancar proses pendidikan dalam pendayagunaan potensi ekonomis secara kreatif dan inovatif dengan terencana secara sistematis dan dapat dievaluasi secara benar sehingga mencapai tujuan yang diharapkan. Pesantren Pertanian Darul Fallah Bogor adalah lembaga pendidikan yang berfokus pada pengembangan diri peserta didiknya dibidang kewirausahaan sehingga dapat menghasilkan generasi yang berjiwa mandiri.Jenis penelitian ini merupakan penelitian kualitatif, dengan pendekatan studi kasus.Dalam pengumpulan data penulis menggunakan metode observasi, wawancara dan dokumentasi.Hasil dari penelitian menunjukan bahwa Pesantren Pertanian Darul Fallah Bogor adalah lembaga pendidikan yang memiliki pola manajemen kewirausahaan pesantren yang sesuai dengan konsep manajemen kewirausahaan pesantren.Dibuktikan dengan kontribusi riil lulusan alumni Pesantren Pertanian Darul Fallah Bogor.KATA KUNCI: entrepreneurship, jiwa, kewirausahaan, manajemen, pesantren. ENTREPRENEURIAL MANAGEMENT OF ISLAMIC BOARDING SCHOOL IN FOSTERING THE ENTREPRENEURSHIP SPIRITABSTRACTEntrepreneurial management Islamic boarding school the utilization of economic potential in a creative, innovative, and courage to face risks to earn profits by systematically planned and can be evaluated properly, accurate, and complete so as to achieve objectives in a productive, high quality, effective and efficient. Entrepreneurial management so that schools can also be regarded as an element in education for the success of the program in educational organizations and expediting the process of education is not as excessive media benefit. Agriculture Darul Fallah Bogor Islamic boarding school is the institution that is a focus on self-development in entrepreneurship so that learners can product independently minded generation. From this background, the authors are interested in examining these educational institutions with the aim to determine the application of entrepreneurial management schools, the impact of the application of entrepreneurial management schools in growing spirit of entrepreneurship and entrepreneurial management Islamic boarding school real contribution in fostering entrepreneurship spirit. The result of research shows that Agriculture Darul Fallah Bogor Islamic boarding school is an educational institution that has a pretty good entrepreneurial management pattern. It is proved by the existence of entrepreneurship management that can develop entrepreneurship spirit of students and real contribution from entrepreneurship management that is material contribution so that can help in boarding school economy, moral contribution in the form of support from various cooperation partners that can give benefit to boarding school. And contribution from graduated Agriculture Darul Fallah Bogor Islamic boarding school who has become a successful entrepreneurship in helping pesantren in the form of material and training for the students.